1996
DOI: 10.1021/jp960257c
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Model Calculations of the Proton Affinities of Aminoalkanes, Aniline, and Pyridine

Abstract: It is shown that the MP2(fc)/6-311+G**//HF/6-31G*+ZPE(HF/6-31G*) theoretical model reproduces very well the experimental proton affinities (PAs) of aminoalkanes and of some of their fluoro derivatives as well as the PAs of aniline and pyridine. In all molecules considered the nitrogen is most susceptible to proton attack. PA values of amino derivatives including aniline are shown to be linearly dependent on the nitrogen lone-pair s character. Increments I(X)α are derived for the amino group and the pyridine ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
56
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 23 publications
9
56
0
Order By: Relevance
“…The optimized structure of 1 was similar to those from previous ab initio calculations11,32 and showed a reasonable agreement with experimental data. 33 The calculated proton affinities for N, C-2, C-3 and C-4 (Table 2) agreed closely with those reported by Hillebrand et al 4 and showed that the nitrogen atom must be the preferred protonation site in 1. The proton affinity of 1 was in excellent agreement with the tabulated value (924 kJ mol~1).2 The data also showed that pyridine should be protonated exclusively at N with gasphase acids of PA P 690 kJ mol~1 to give the single pyridinium isomer 1H`.…”
Section: D~supporting
confidence: 87%
“…The optimized structure of 1 was similar to those from previous ab initio calculations11,32 and showed a reasonable agreement with experimental data. 33 The calculated proton affinities for N, C-2, C-3 and C-4 (Table 2) agreed closely with those reported by Hillebrand et al 4 and showed that the nitrogen atom must be the preferred protonation site in 1. The proton affinity of 1 was in excellent agreement with the tabulated value (924 kJ mol~1).2 The data also showed that pyridine should be protonated exclusively at N with gasphase acids of PA P 690 kJ mol~1 to give the single pyridinium isomer 1H`.…”
Section: D~supporting
confidence: 87%
“…7,8 An alternative pathway is based on the HF/6-31G* optimization of structures followed by the single-point MP2 calculation, as will be discussed later. 9,10 Our relatively simple theoretical model gave results in excellent accordance with the best available experimental data for the first-row atoms. Furthermore, we have been able to show that PAs in heavily substituted benzenes follow a transparent rule rooted in the independent substituent approximation (ISA).…”
Section: Introductionsupporting
confidence: 80%
“…Substitutional effects on proton affinities are well-known and substantial. [30][31][32][33][34][35][36] For a consistent set of comparisons, we computed the product structures and protonation energies of all the amines in Table 1. These computed results can be directly compared with tabulated gas-phase amine basicities, defined as the free energy of the protonation reaction, which we have taken from the NIST WebBook.…”
Section: Amine Protonationmentioning
confidence: 99%